Effects of Mineral Oils on Host Selection Behavior of Diaphorina citri - Mofit Eko Poerwanto; Y. Andi Trisyono; Siti Subandiyah; Edhi Martono; Paul Holford; George Andrew Charles Beattie (Universitas Gadjah Mada, 2008)
Response of Diaphorina citri Kuwayama (Hemiptera: Psyllidae) on citrus leaves treated with horticultural and agricultural mineral oil (HMO & AMO) was evaluated under laboratory condition in choice and non-choice trials. Combination of HMO and AMO at concentration of 0 up to 2% was applied to citrus leaves. Mineral oil applications significantly reduced the proportion of D. citri stayed on citrus leaves for feeding with the proposed mechanisms: 1) oils covered leaves thus hampered it for releasing volatile compounds, 2) oil film preventing the direct contact of tarsus or palpus to leaf surfaces, and 3) the volatile compounds produced by mineral oils also blended with plant volatiles in the atmosphere and reduced the probability of olfactory receptors capturing the olfactory cues for locating the feeding site. Mineral oils also increased the mortality of D. citri due to the refusion for feeding on the treated citrus leaves. The effect of AMO was more prominent than HMO.